Knowledge Management for Maintenance Activities in the Manufacturing Sector - Muhamad Arifpin, Mansor; A., Ohsato; S., Sulaiman (Universiti Malaysia Pahang, 2012)

(untitled)
Maintenance is an indispensable part of the business process and plays an important role in an organisation’s success and survival. The main purpose of maintenance is to ensure equipment functions at its original optimal level. Thus, the knowledge and skills of operators are crucial and in demand. This paper presents a knowledge management of maintenance activities transfer method. Knowledge management is a process that a company cannot avoid, because it is a step in providing the necessary information for business performance measurements. Based on the example of a knowledge management system for a consultant company, we propose a knowledge repository or warehouse for maintenance activities that consists of four elements: best practice, databases, discussion forums and assessment tools. Each element has its own role and contribution towards better maintenance activities. Therefore, knowledge management has a deep relationship with performance evaluation or measurement.